Analysis of the Business Feasibility Study of the Development of UMKM Tempe Pak Muhlis, Lerpak Village, Geger District, Bangkalan District, Perspective of Management Aspects - Helmi (Managing: Jurnal Bisnis dan Manajemen, 2024)
This study aims to determine the business feasibility of the development of Tempe Pak Muhlis MSMEs in Lerpak Village, Geger District, Bangkalan Regency, in the Management aspect. Management is the achievement of business goals in an effective and efficient manner through planning, organizing, leading and controlling business resources. In order to achieve the goals or objectives of a business, of course, through a management process. Tempeh is one of the foods favored by the community. The raw material for making tempeh comes from soybeans and non-soybeans. The business of making tempeh in Indonesia is mostly done in the home industry or home industry, one of which is like the one in Geger District Dusun Lerpak Kab. Bangkalan. this study aims to identify the feasibility of the tempeh industry in Lerpak Hamlet from the management aspect through a qualitative approach. data collected through in-depth interviews with producers of shrimp paste traders and consumers as well as direct observation in the field. Based on the results of the research, the tempeh industry can be said to be feasible because it has covered and fulfilled the analysis method.